(untitled) (Theatrum historiae, 2015)
The article analyses plans for a Polish-Czechoslovak (con)federation and their role in the foreign policy of the Polish Government-in-Exile. The aims of the article are twofold. Firstly, to explore long-term goals set by the Polish Government for the union of the two countries, especially those connected with the post-war stability and safety of this European region. Secondly, to present the immediate goals of strengthening the Polish Government’s position and its current policy.